Web shear buckling of steel–concrete composite girders in negative-moment regions. (15th June 2021) - Men, Pengfei; Di, Jin; Jiang, Hongyi; Zhou, Xuhong; Qin, Fengjiang
Highlights: Web shear buckling of composite girders in negative-moment regions is studied. A 3D nonlinear finite element prediction model is developed and validated. Top flange and slab together provide fixed boundary condition on one edge for web. A new formula for web shear-buckling coefficients of composite girders is proposed. Abstract: Steel–concrete composite girder webs used to connect flanges in bridges are generally slender, which introduces stability problems. The assumption in existing codes that the web is simply supported on four sides is excessively conservative and unreasonable. In this study, web shear buckling of steel–concrete composite girders in negative-moment regions were experimentally and numerically investigated. The failure modes, shear-buckling loads, and ultimate loads of the specimens were analysed. Based on the surface strain and out-of-plane deflection of the web, the web shear-buckling load was determined and compared with the theoretical results. A three-dimensional non-linear finite element model is developed and validated based on the experimental results. Using the validated numerical model, the elastic shear-buckling behaviour of the webs of composite girders under actual boundary conditions were investigated. The numerical results showed that the boundary conditions of the composite girder web can be regarded as simply supported on two opposite edges, fixed on one edge, and restrained by the bottom flange on one edge. A formula for calculating the web shear-buckling coefficient of composite girders was proposed based on the numerical results.